EFL STUDENTS’ RESPONSE TO INDIRECT CORRECTIVE FEEDBACK IN WRITING FOR GENERAL COMMUNICATION COURSE - Rissa San Rizqiya; Siska Rizkiani; Gartika Pandu Bhuana (IKIP Siliwangi Bandung, 2020)
Written corrective feedback aims at developing students writing proficiency where they are aware of what is expected as writers and are capable to create text with minimal errors and maximum clarity. This study aims at finding the students’ response towards teacher’s coded and uncoded written corrective feedback on their writing. A total of 79 freshmen majoring English Education Study Program of IKIP Siliwangi participated in filling questionnaire and twelve of them were interviewed using a semi-structured format. Qualitative method was applied in conducting this study. The data were labeled, coded and categorized in four dimensions: value, positivity, participation, and evaluation. The findings showed that in term of value students who got coded feedback showed positive opinion; while students who got uncoded feedback felt confusion. Further, in terms of positivity, participation and evaluation both classes showed positive response. Both classes agree they favor the teacher to provide the feedback by giving a mark, suggesting error correction, and providing written comments on the content. To conclude, students approve written corrective feedback on condition that teacher provides suggestions to improve their writing. Thus, it is suggested for the teacher to consider the feedback types in correcting the students’ written error.